The anterior cingulate cortex and its interface with the dorsal periaqueductal grey regulating nitric oxide-mediated panic-like behaviour and defensive antinociception - Falconi-Sobrinho, Luiz Luciano; Anjos-Garcia, Tayllon dos; Rebelo, Macário Arosti; Hernandes, Paloma Molina [UNESP]; Almada, Rafael Carvalho [UNESP]; Tanus-Santos, Jose Eduardo; Coimbra, Norberto Cysne (Elsevier, 2024)
The anterior cingulate cortex (ACC) Cg1 (24b) area modulates glutamate-mediated unconditioned fear and antinociception organised by hypothalamus. However, it remains unknown whether 24b area also modulates these latter defensive responses through connections with the dorsal periaqueductal grey matter (dPAG), a midbrain structure implicated in the genesis of innate fear-induced defence. The aim of this work is to examine the correlation between the behavioural effects of intra-ACC microinjections of vehicle, NMDA (1 nmol) or lidocaine (2%) with Fos protein expression and nitrergic activity in the dPAG of male C57BL/6 mice that were threatened by snakes. In addition, the 24b area-dPAG pathways were also characterised by neural tract tracing procedures. Finally, the effect of dPAG pretreatment with the neuronal nitric oxide synthase inhibitor N(omega)-propyl-L-arginine (NPLA; 0.2, 0.4 or 0.8 nmol) 10 min before 24b area treatment with NMDA on behavioural and nociceptive responses of threatened mice was studied. The activation of 24b area N-methyl-D-aspartic acid receptors facilitated escape and freezing rather than risk assessment, and enhanced Fos expression and nitrite levels in dPAG, while lidocaine decreased escape and risk assessment as well as Fos and nitrergic activity in dPAG. In addition, dPAG pretreatment with NPLA suppressed intra-24b NMDA-facilitated panicogenic effects while increased nociception. Infusions of an antegrade neurotracer into 24b area showed axonal fibres surrounding both dorsomedial and dorsolateral PAG perikarya. Neurons were identified in 24b area after deposits of a retrograde neurotracer into dPAG. Our findings suggest that the ACC/24b area modulates innate defensive responses through the recruitment of dPAG nitrergic neurons.
Keywords: Anterior cingulate cortex; Crotalus durissus terrificus; Defensive behaviour; Fear-induced analgesia; Nitric oxide; NMDA receptors; Periaqueductal grey matter